Multimedia Network Intergation and Management - Larry L. Ball (New York(State): McGraw-Hill, 1996)
This unique reference guide provides you with comprehensive coverage of the architectures, controls, signaling and modality, and applications requirements needed to cope successfully with the new and complex technical management issues relating to multimedia networks.
(NP(B/14092, (NP(B/14091s
+Photos
Keywords: technologies -- network -- management -- functions